Manajemen Layanan Khusus Osis di SMA Unggulan Bppt Darus Sholah - Riyana Dwi Anggraini; Arina Mahdiana; Siti Nur Azizah; Saifatil Kamila; Rofiq Hidayat (Pondok Pesantren As-salafiyah Asy-syafi'iyyah, 2023)
This study aims to analyze the implementation of OSIS (Intra-School Student Organization) special service management at Darus Sholah High School. The management of OSIS special services represents a crucial approach to organizing and overseeing various programs and activities carried out by the student organization within the school environment. According to Baharuddin, the scope of OSIS special services encompasses the processes of planning, organizing, implementing, and evaluating the services provided by OSIS for the benefit of students and the school community. The primary goal is to enhance students’ overall school experience, promote leadership development, and foster a positive and supportive learning environment. This research employed a qualitative method, with data sources drawn from the school principal and the Deputy Head of Student Affairs. Data were collected through observations, interviews, and documentation techniques. The analysis process included data condensation, data presentation, conclusion drawing, and verification, supported by triangulation to ensure data validity. The analytical framework was based on Baharuddin’s theoretical perspective. The findings reveal that the implementation of special OSIS service management enables the organization to play a significant role in strengthening social relationships among students, facilitating learning processes, and encouraging active student participation in various extracurricular activities. Furthermore, it contributes to the development of essential soft skills, including leadership, teamwork, collaboration, and responsibility, thereby enriching the students’ personal and academic growth.